Characterization of Mayaro virus (strain BeAn343102) biology in vertebrate and invertebrate cellular backgrounds. (10th October 2022) - Pujhari, Sujit; Brustolin, Marco; Heu, Chan C.; Smithwick, Ronald; Larrosa, Mireia; Hafenstein, Susan; Rasgon, Jason L.
Abstract : Mayaro virus (MAYV) is an emerging New World alphavirus (genus Alphavirus, family Togaviridae ) that causes acute multiphasic febrile illness, skin rash, polyarthritis and occasional severe clinical phenotypes. The virus lifecycle alternates between invertebrate and vertebrate hosts. Here we characterize the replication features, cell entry, lifecycle and virus-related cell pathology of MAYV using vertebrate and invertebrate in vitro models. Electron-dense clathrin-coated pits in infected cells and reduced viral production in the presence of dynasore, ammonium chloride and bafilomycin indicate that viral entry occurs through pH-dependent endocytosis. Increase in FITC-dextran uptake (an indicator of macropinocytosis) in MAYV-infected cells, and dose-dependent infection inhibition by 5-(N-ethyl-N-isopropyl) amiloride (a macropinocytosis inhibitor), indicated that macropinocytosis is an additional entry mechanism of MAYV in vertebrate cells. Acutely infected vertebrate and invertebrate cells formed cytoplasmic or membrane-associated extracytoplasmic replication complexes. Mosquito cells showed modified hybrid cytoplasmic vesicles that supported virus replication, nucleocapsid production and maturation. Mature virus particles were released from cells by both exocytosis and budding from the cell membrane. MAYV replication was cytopathic and associated with induction of apoptosis by the intrinsic pathway, and later by the extrinsic pathway in infected vertebrate cells. Given that MAYV is expanding its geographical existence as a potential public health problem, this study lays the foundation for biological understanding that will be valuable for therapeutic and preventive interventions.